(untitled) (Jurnal Bina Praja, 2020)
Local fiscal autonomy of Bogor Regency is still low, due to the low contribution of local own revenue to total local revenues. This fact has implications for the high local financial dependence on fiscal transfer from the central government, so that the Bogor Regency government is not yet autonomous in financing local development programs. This research aims to obtain rational knowledge about the effects of fiscal decentralization implementation and indirect local tax management on local fiscal autonomy. The research used a descriptive method with a qualitative approach, so that it can explain data and information obtained from observation, interview, and focus group discussion. The research concludes that the prospect of raising local fiscal autonomy is determined by the accuracy of fiscal decentralization implementation and the effectiveness of indirect local tax management. The accuracy of fiscal decentralization implementation requires the central government policy in the assignment of taxes and revenue sources to local government must be commensurate with the assignment of expenditure responsibilities to local government. The effectiveness of indirect local tax management requires that local government efforts to increase indirect local tax revenues must precisely determine the increase of revenue targets according to the results of econometric analysis of Gross Domestic Regional Product (GDRP) on certain sectors, improving the ability of local tax apparatus, and improving the obedience of indirect local taxpayer.